Tau-mediated Neurodegeneration and Potential Implications in Diagnosis and Treatment of Alzheimer's Disease - Wu, Xi-Lin; Piña-Crespo, Juan; Zhang, Yun-Wu; Chen, Xiao-Chun; Xu, Hua-Xi (Chinese medical journal, 2017)
To review recent research advances on tau, a major player in Alzheimer's disease (AD) pathogenesis, a biomarker for AD onset, and potential target for AD therapy. This review was based on a comprehensive search using online literature databases, including PubMed, Web of Science, and Google Scholar. Literature search was based on the following keywords: Alzheimer's disease, tau protein, biomarker, cerebrospinal fluid (CSF), therapeutics, plasma, imaging, propagation, spreading, seeding, prion, conformational templating, and posttranslational modification. Relevant articles were carefully reviewed, with no exclusions applied to study design and publication type. Amyloid plaques enriched with extracellular amyloid beta (Aβ) and intracellular neurofibrillary tangles comprised of hyperphosphorylated tau proteins are the two main pathological hallmarks of AD. Although the Aβ hypothesis has dominated AD research for many years, clinical Aβ-targeting strategies have consistently failed to effectively treat AD or prevent AD onset. The research focus in AD has recently shifted to the role of tau in AD. In addition to phosphorylation, tau is acetylated and proteolytically cleaved, which also contribute to its physiological and pathological functions. Emerging evidence characterizing pathological tau propagation and spreading provides new avenues for research into the molecular and cellular mechanisms underlying AD pathogenesis. Techniques to detect tau at minute levels in CSF and blood have been developed, and improved tracers have facilitated tau imaging in the brain. These advances have potential to accurately determine tau levels at early diagnostic stages in AD. Given that tau is a potential therapeutic target, anti-tau immunotherapy may potentially be a viable treatment strategy in AD intervention. Detecting changes in tau and targeting tau pathology represent a promising lead in the diagnosis and treatment of AD.